Zonal Policy of Special Economic Zones According to Country Classifications by Income Level and the Growth of Special Economic Zones in Uzbekistan - Mirhamidova Zahinabonu Mirhamidkizi; Mirhamidova Zahinabonu Mirhamidkizi (International Journal on Economics, Finance and Sustainable Development, 2021)
This article examines the concept of special economic zones, their types and main benefits provided to the residents. We consider economic, social, scientific and technical aspects of special economic zones. Special economic zones are reshaping the world economy. Special economic zones have been established in many countries as a mechanism to attract foreign direct investment, accelerate industrialization and create jobs. Not all special economic zones have been successful, and this paper examines the key parameters that contribute to the success of special economic zones, as well as the objectives of zone policy and the predominant zone types as classified by countries around the world.